2006
DOI: 10.1159/000095069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early High-Dose Levothyroxine Treatment on Auditory Brain Event-Related Potentials at School Entry in Children with Congenital Hypothyroidism

Abstract: Aims: We tested whether brain event-related potentials (ERPs) are normal in children with congenital hypothyroidism (CH) after early high-dose levothyroxine treatment. Methods: Auditory ERPs were recorded in 33 normal controls and in 15 children with CH at 5 years 9/12. Based on bone maturation at diagnosis, the CH group was divided into severe (n = 8) and moderate (n = 7) subgroups. CH patients were treated at a median age of 14 days with a mean initial dose of levothyroxine of 11.6 µg/kg·day. Two ERP compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
11
0
3
Order By: Relevance
“…Simoneau et al [21] reported that the number of times the plasmatic thyrotropin (TSH) was above normal ranges during treatment was positively correlated to anxiety and inattention, while the number of times TSH was below normal correlated with inferior verbal punctuation. Also, Marti et al [22] found a greater latency in the auditory N200 component of cognitive potentials in the CH group as compared to healthy controls. Furthermore, the latency increased with excessive initial treatment, suggesting a potentially harmful effect of a high initial dose.…”
Section: Introductionmentioning
confidence: 99%
“…Simoneau et al [21] reported that the number of times the plasmatic thyrotropin (TSH) was above normal ranges during treatment was positively correlated to anxiety and inattention, while the number of times TSH was below normal correlated with inferior verbal punctuation. Also, Marti et al [22] found a greater latency in the auditory N200 component of cognitive potentials in the CH group as compared to healthy controls. Furthermore, the latency increased with excessive initial treatment, suggesting a potentially harmful effect of a high initial dose.…”
Section: Introductionmentioning
confidence: 99%
“…El manejo farmacológico y clínico permite mejorar el IQ rápidamente en comparación con los niños que no han recibido tratamiento, incluso aquellos que han sido tratados podrían alcanzar un crecimiento, desarrollo y peso normal para su edad 45 . Además, se ha informado mejora en el estado de ánimo y la función neuropsicológica en pacientes que han sido tratados con una combinación de hormonal T4 y T3 49 ; y mejora en los cambios del desarrollo psicomotor y del lenguaje con el empleo oportuno y temprano de levotiroxina 46,48 . Dentro de las consecuencias negativas del tratamiento por ejemplo podemos encontrar variaciones en el peso que aún no se han correlacionado con niveles hormonales de THS; y compromiso de la inteligencia, donde se evidencian disminuciones del IQ, de 5 a 10 puntos 47 .…”
Section: Pronóstico De La Enfermedadunclassified
“…Es un indicador muy sensible pero inespecífico porque se obtiene independientemente de la modalidad sensorial de los estímulos: visual o auditivo. Hansenne (2000) expone una amplia gama de usos del P300 para la investigación clínica, y usualmente es un indicador que se usa para detectar daños sutiles en los procesos atencionales (Alonso et al, 2002;Marti et al, 2006).…”
Section: Componente P300unclassified